2013
DOI: 10.5194/se-4-1-2013
|View full text |Cite
|
Sign up to set email alerts
|

Application of titanium-in-quartz thermobarometry to greenschist facies veins and recrystallized quartzites in the Hsüehshan range, Taiwan

Abstract: Abstract. The accuracy, reliability and best practises of Tiin-quartz thermobarometry (TitaniQ) in greenschist facies rocks have not been established. To address these issues, we measured Ti concentrations in rutile-bearing samples of moderately deformed, partially recrystallized quartzite and vein quartz from the Hsüehshan range, Taiwan. The spread of Ti concentrations of recrystallized grains in quartzite correlates with recrystallized grain size. Recrystallized quartz (grain size ∼100-200 µm) that formed du… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(67 citation statements)
references
References 57 publications
(109 reference statements)
3
64
0
Order By: Relevance
“…Thus, to know which of these schemes is true in the case of our study area, information about the metamorphic evolution of the footwall and hanging wall formations is essential. This information can be determined using the chemical compositions of the available quartz grains based on the ''Ti-in-quartz'' thermometer (Wark and Watson 2006;Thomas et al 2010;Huang and Audétat 2012;Kidder et al 2013;Haertel et al 2013). If the metamorphic grades of the footwall and hanging wall formations are nearequivalent, then the coincidence of the brittle and ductile shear zones could be caused by primarily evolved softened regions.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, to know which of these schemes is true in the case of our study area, information about the metamorphic evolution of the footwall and hanging wall formations is essential. This information can be determined using the chemical compositions of the available quartz grains based on the ''Ti-in-quartz'' thermometer (Wark and Watson 2006;Thomas et al 2010;Huang and Audétat 2012;Kidder et al 2013;Haertel et al 2013). If the metamorphic grades of the footwall and hanging wall formations are nearequivalent, then the coincidence of the brittle and ductile shear zones could be caused by primarily evolved softened regions.…”
Section: Discussionmentioning
confidence: 99%
“…We note that both these anomalous results and those of Kidder et al (2013), who found a brighter blue CL signal in recrystallized areas, were observed in quartz with Ti concentrations much lower than measured by Wark and Spear (2005).…”
Section: Cathodoluminescencementioning
confidence: 57%
“…The typical association of recrystallized grains with darker-CL and low Ti (e.g. Kidder et al, 2013) was rarely observed in the mylonites and protomylonites, but is common in the ultramylonites. The sample analyzed using hyperspectral CL has a Solid Earth Discuss., https://doi.org/10.5194/se-2018-12 Manuscript under review for journal Solid Earth Discussion started: 7 March 2018 c Author(s) 2018.…”
Section: Cathodoluminescencementioning
confidence: 99%
See 2 more Smart Citations